(untitled) (Research, Society and Development, 2021)
This research, developed with Integrated High School (EMI) students at the Triângulo Mineiro Federal Institute - Campus Uberaba (IFTM-URA), was motivated by the occurrence of acts of depredation of public school property (PPE), in the pre- pandemic, and the need for a pedagogical intervention to raise awareness for the preservation of the PPE was perceived. During the Covid-19 pandemic, this research developed an audiovisual, called Usinagem FotoVídeo, where students reported the importance of the school space for them. The audiovisual was viewed by 94 students and 91% informed that the FotoVídeo Usinagem contributed to the awareness of the PPE and 97% evaluated as important the role of the student in institutional actions. It concludes that audiovisual production as a tool for learning can be used by educators, regardless of their area of expertise, therefore, it is essential that students are motivated so that this modal is closer to entertainment, leisure and that learning is a consequence.